THE ANTIBIOFILM ACTIVITY OF HIBISCUS SABDRIFFA L. AGAINST METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS - & Gharb, Jaddoa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The current study was aimed to investigate the antibacterial and antibiofilm activity of ethanolic extract of Hibiscus sabdariffa L. calyx against locally isolated methicillin-resistant Staphylococcus aureus (MRSA) at different concentrations were started from 0.078 to 40 mg/ml. The extract was prepared by soaked calyces powder of Hibiscus sabdariffa L. with 80% ethanol in the Soxhlet extraction unit, and then it was aseptically filtered. The antibacterial activity was tested by agar diffusion method and broth microdilution method, this method was used to determine the minimum inhibitory concentration of extract, while the antibiofilm activity was determined by using 96-well polystyrene microtiter plates. The results revealed that the ethanolic extract has antibacterial activity in a concentration-dependent manner, the average diameter zone of inhibition observed against MRSA isolates ranged from 14±0.5 mm to 20±0.5 mm Moreover, at sub-inhibitory concentration, this extract developed an isolate-specific antibiofilm effect and presented highly significant (P< 0.05) variability in biofilm formation before and after addition of ethanolic extract, Mr1, and Mr7 isolates were gave the lowest and highest antibiofilm activity, respectively. In conclusion, the ethanolic extract of H. sabdariffa L. calyx is a promising alternative medication that can be used to treat the infection caused by MRS.